Measuring the prevalence of self-managing teams: taking account of defining characteristics - Nijholt, Jurriaan J.; Benders, Jos (Work, employment and society, 2010)
Self-managing teams are considered a hallmark of employee participation and high-performance work practices. However, the results of research into their prevalence are usually incomparable, since sources use varied and divergent operationalisations. Building on recent studies that measure team prevalence, we propose our own operational definition of teams, and suggest suitable items for their measurement. We thereby aim to encourage standardisation in the measurement of team prevalence.